Nonlinear pH Control Based on Reaction Invariant and Self-Tuning PID Controller - Cordova, Hendra; Justiono, Heri; Masduki, Ali (IPTEK The Journal for Technology and Science, 2025)
pH neutralization process analytical model represents two processes dynamic. They mix reaction and reaction invariance that are achieved by solving the nonlinear electric charge balance acid-base. Reaction invariants are quantities that take the same values before, during and after a reaction. We identify a set of reaction invariants that are linear transformations of the species mole numbers. The material balances for chemically reacting mixtures correspond exactly to equating these reaction invariants before and after reaction has taken place. This research used HCl (strong acid) that is titrated by NaOH (Strong Base). All dynamic will perform nonlinear model, so we need the nonlinear controller scheme too. Therefore we choose the Self-Tuning- Controller (STCPID) that is part of adaptive control which has ability to handle nonlinearity and process load change. To find Figure of merit the STC in this work the control system compare with PID conventional controller scheme. The simulation result has a good and suitable performance under several tests (set-point and load change).